Adult Onset Best Vitelliform Macular Dystrophy: A Case Report - Gupta, Sharad; Sharma, Hari; Yadav, Reena; Singh, Sanjay Kumar; Chaudhary, Sushma (Journal of Lumbini Medical College, 2020)
Introduction: Best disease or vitelliform macular dystrophy is a rare autosomal dominant disorder with bilateral presentation characterized by subretinal accumulation of yellowish material in the macular area. Macular findings range from a small yellow spot, multiple vitelliform or atrophic lesions to a chorio-retinal scar. Case report: A 35 years male presented to our outpatient department with chief complaint of blurring of vision of both eyes for the past three months. His visual acuity was 6/12 in both right and left eyes. On slit-lamp bio-examination anterior segments of both eyes were normal. On fundus examination, both eyes revealed a single, circular, yellow-opaque egg yolk-like macular lesion with no other abnormalities. Optical coherence tomography of both eyes revealed deposits of homogenous hyper- reflective material beneath retinal pigment epithelium at fovea. Fundus fluorescence angiography showed blocked fluorescence at the site of vitelliform lesion of both eyes. Conclusion: Best vitelliform macular dystrophy is a rare genetic disorder with incomplete penetrance. Optical coherence tomography and fundus fluorescence angiography support the diagnosis.